Guest of the Festival Georgi Stanishev (Bulgaria) - Tkacheva, Marina (project baikal, 2017)
The interview contains discussion of social problems of interrelations between the capital and the periphery, functions and possibilities of the periphery, and significance of cultural factors for the dynamics of cities. The interview touches upon the processes of modern urbanization, as well as spontaneity and regularity of construction of contemporary cities. The hybrid character of the strategies for new centers is highlighted. The necessity to work out an independent strategy for development of peripheral territories is discussed.